2019
DOI: 10.3390/ani10010026
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Rabbit-Assisted Interventions in the Classroom Environment

Abstract: The effect of rabbit-assisted interventions on the anxiety levels of first-grade children at a primary school was analyzed. At the beginning of our research, no rabbit-assisted intervention was applied for 6 weeks in order to establish the level of stress caused by the start of the education period. We then alternated 6-week-long periods with and without rabbit-assisted intervention. The level of anxiety in children was assessed every three weeks both in the assisted and non-assisted periods, using the State–T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
10
0
3
Order By: Relevance
“…The presence of the rabbit reduced children's anxiety levels by 9.48% in the inclusive schools and by 7.24% in the regular school. At the same time, however, the research did not provide any findings connected to the behaviour of the animals and their stress levels [11].…”
Section: Studies Made With Rabbits: Previous Research Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The presence of the rabbit reduced children's anxiety levels by 9.48% in the inclusive schools and by 7.24% in the regular school. At the same time, however, the research did not provide any findings connected to the behaviour of the animals and their stress levels [11].…”
Section: Studies Made With Rabbits: Previous Research Resultsmentioning
confidence: 88%
“…The strong stress effect deteriorated the previously established relationship, so the interoperability of the rabbits might have been replaced by fear, indifference or perhaps even aggression. Based on the research study, it was suggested that rabbits should receive handling for 2-3 weeks before starting therapy [30].…”
Section: Studies Made With Rabbits: Previous Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The school counselor works with the child’s teacher who has a litter box trained rabbit in the classroom. Opportunities to interact with the bunny motivate the child to attend school and have more positive attitudes Rabbits in the classroom (Molinar et al, 2020 ) Welfare of rabbits (Royal Society for the Prevention of Cruelty to Animals, 2019 ) Encourage participation in learning activities (Gee et al, 2017 ) such as reading aloud (Levinson et al, 2017 ) A first grader who transfers into a new school midyear is a reluctant reader who and sometimes refuses to read aloud. The school counselor considers it to be a case of reading anxiety.…”
Section: Rationale For Animal-assisted Therapymentioning
confidence: 99%
“…Although slightly different in their overall approach, both animal-assisted activities (AAA) and animal-assisted therapies (AAT) have been found to be effective in managing anxiety and depression in both children and adults (Molnár et al, 2020 ; Murray et al, 2019 ; Waite et al, 2018 ; Wilson et al, 2017 ). As such, complementary therapies such as AAT could be viable for use alongside traditional pharmacological and talking treatments.…”
Section: Introductionmentioning
confidence: 99%